Outcome and prognostic factors in high‐risk childhood adrenocortical carcinomas: A report from the European Cooperative Study Group on Pediatric Rare Tumors (EXPeRT). Issue 6 (13th December 2016) - Cecchetto, Giovanni; Ganarin, Alba; Bien, Ewa; Vorwerk, Peter; Bisogno, Gianni; Godzinski, Jan; Dall'Igna, Patrizia; Reguerre, Yves; Schneider, Dominik; Brugières, Laurence; Leblond, Pierre; Ferrari, Andrea; et al.
Abstract: Objectives: The aim of this retrospective international analysis was to evaluate the role of risk factors in pediatric patients with adrenocortical carcinoma (ACC) observed in European countries (2000–2013) in an attempt to identify factors associated with poor prognosis. Procedures: Data were retrieved from databases of Germany, France, Poland, and Italy, which form the European Cooperative Study Group on Pediatric Rare Tumors (EXPeRT). Patients were less than 18 years old, with at least one of the following tumor‐related risk factors: metastases, volume more than 200 cm 3, Cushing syndrome, vascular or regional lymph node invasion, initial biopsy, or incomplete excision. Role of patients' age was also evaluated. Results: Eighty‐two patients were evaluated: 62 with localized disease and 20 with metastases. The 3‐year progression‐free survival (PFS) and overall survival (OS) were 39% and 55% for the whole population, respectively, and 51% and 73% for localized diseases, respectively. Concerning the whole population, PFS and OS were influenced by distant metastases, tumor volume, lymph node involvement, age, and presence of two or more risk factors. Factors significant only at OS were vascular involvement and incomplete surgery. At multivariable analysis, the main factors at PFS were volume more than 200 cm 3 (hazard ratio [HR]: 2.6, 95% confidence interval [CI]: 1.18–5.70) and presence of distant metastases (HR: 8.26, 95% CI: 3.49–19.51). The OS was significantly influenced by the presence of metastases ( P < 0.0001). Concerning patients with localized tumors, the only significant prognostic factor was volume more than 200 cm 3 with a HR of 4.38 (95% CI: 1.60–12.00) for PFS and of 3.68 (95% CI: 1.02–13.30) for OS. Conclusions: Distant metastases and large tumor volume were the main unfavorable prognostic factors. Presence of two or more factors related to ACC was associated with an aggressive behavior of disease.